Peran Pendidikan Islam Dalam Pembentukan Moral Bangsa - Abd Rahman (Al-Riwayah : Jurnal Kependidikan, 2015)
Education is a pillar for a nation to move forward. Education serves to produce the nation’s future generation having strong intelectual capability accompanied with good character and good morals. However, generally education is only able build the intelectual aspect and fail in the spiritual intelligence. Lately signs of decadence or moral degradation experienced by the public is also increasingly emerging. Violence, fights, sexual harassment, drugs, corruption have become a phenomenon and consumption of media every day. Acceleration of development we have achieved is not followed by a strong moral nation. Although Islam is embraced by the majority population of Indonesia but in application the values embodied in the teachings of Islam is only understood teoritically. It just is not grounded in the applicative level. Islamic education is therefore expected to become one of the main variables that can perform a strategic role in the formation of the nation’s morals. Islamic education is expected to play a role in the development of identity and national character. With the spiritual and moral growth it shapes this nation to be individuals who have a high intelectual capacity and high values of morality.